The Problem of Online Learning in Islamic Primary School in Yogyakarta - Nana Apriliana (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2021)
In the rapid development of religion-based schools in Indonesia, especially Islam, this study intended to determine the problems experienced by students, parents, and teachers in Islamic primary school (Madrasah Ibtidaiyah) during online learning due to the pandemic Covid-19. This was a descriptive study using the online survey method. The data was collected using online open-ended questionnaires to 136 participants of elementary school students, parents, and teachers. It was found that students preferred play to study, they were lack of discipline in learning and felt bored studying at home. Whereas, the entire phone's memory, unstable internet connection, and lack of budget for internet connection were the most obstacle factors faced by parents and teachers. The teachers also had unlimited working time. Parents were also challenging to explain the materials for their children, challenging to build students' motivation, difficult to divide the time between work and guide their children to study. Therefore, the researcher recommends (1) applying learning rules to discipline students learning activities during online learning, (2) consulting with teachers or find appropriate sources to explain difficult materials i.e. free access to online learning media provided by the Ministry of Education and Culture (MoEC) to enrich learning sources, (3) creating a comfortable learning atmosphere, trying to learn outdoor and interspersed with fun activities are essential methods to kill children boredom in online learning, and (4) equipping teachers with online learning skills i.e. the use of technology, software, and teaching online method in long term teacher education program (Pendidikan Profesi Guru/PPG) to improve teachers' teaching quality in online teaching.